Development of a Student Code of Conduct Information System Using the Laravel and Agile Methodology at SMKN 1 Bonjol - Rahmi Fadila; Ami Anggraini Samudra; Herisvan Hendra (Jurnal Sistem Informasi dan Teknik Informatika (JAFOTIK), 2026)
Managing student discipline at SMKN 1 Bonjol was previously conducted manually using logbooks, which made the process prone to data loss, duplication, and delays in communicating student coaching information to parents. This study aims to design and develop a web-based Student Discipline Information System (SIMTATIB). The research employed a Research and Development (R&D) methodology using the Agile System Development Life Cycle (SDLC), consisting of the Requirement, Design, Development, Testing, Deployment, and Review stages. The system was developed using the Laravel 13 framework, PHP 8.4, and MySQL, and integrated with the WhatsApp Gateway via Fonnte to enable automated notifications. Alpha testing using Whitebox Testing produced acceptable Cyclomatic Complexity values, while Blackbox Testing achieved a 100% success rate. Beta testing based on the ISO/IEC 25010 standard, conducted by system experts, achieved an average score of 96.24%, while evaluation by Counseling Guidance (BK) teachers demonstrated that the system is highly feasible and practical for optimizing student discipline management.